Kinerja Kepolisian Direktorat Lalu Lintas Polda Sulawesi Tengah Dalam Penerapan e-Tilang di Kota Palu - Wati, Nilawati; Mustainnah; Royfandi, Moh. (JPS: Journal of Publicness Studies, 2024)
This study aims to determine the Police Performance of the Central Sulawesi Police Traffic Directorate in the Implementation of E-Tickets in Palu City. The research method used is descriptive qualitative, which provides an overview of the phenomena or factors of the problem under study according to existing facts. Data collection techniques are observation, interviews and documentation of informants totaling 7 people. The theory used is Basri and Rivai, 2015 where there are four indicators, namely the suitability of Planning. Effectiveness of Activity Implementation, Compliance with Regulations, Efficiency of Activities. Based on the results of the study, it can be concluded that the Performance of the Central Sulawesi Police Traffic Directorate in the Implementation of E-Tickets in Palu City in general, its implementation is not fully said to be optimal. This can be seen from the indicators of the research results, including the aspect of compliance with regulations that have not been effective due to the limited range of electronic monitoring and lack of supervision from the police. Therefore, the installation of CCTV on a number of roads in Palu city should have received supervisory assistance from police officers, not only CCTV which is used as a tool to monitor the smooth running of traffic. And the efficiency aspect of the implementation of activities is said to have not run optimally because the use of technology in the implementation of e-Tilang is a major factor because what supports this program is basically using technology, starting from electronic applications to the internet network connection needed. However, in its implementation it is still constrained by the factor of Human Resources (HR) who are still stuttering technology and server problems that have slow connections. And aspects that run optimally are aspects of planning suitability and effectiveness of activity implementation.